IDENTIFIKASI POTENSI LAHAN CARIK INJEMAN, DESA CIBODAS, KABUPATEN BANDUNG SEBAGAI AGROWISATA BERKELANJUTAN - Erlangga Satya Mukti, Erlangga; Etty Indrawati; Nur Intan Simagunsong; Titiek Debora (Jurnal Lingkungan dan Kota, 2023)
Carik Injeman land, Cibodas Village is one of the village lands owned by the local community which is often used for plantation areas for local residents. The plantation area is one of the livelihoods of the local community to improve the economy of Cibodas Village. The Potential of Carik Injeman Land in Cibodas Village is seen to have a lot of potential that allows the rural landscape to be developed. This potential can be developed into a tourism sector that will be able to develop and improve the economy and welfare of the people of Cibodas Village. The development of Carik Injeman Land looks at the potential of the rural landscape which will later function to maintain and also preserve local wisdom, conserve natural resources and also local culture which can improve the quality of the economy and the lives of local people. This rural landscape will later be developed into an Agro-tourism-based tourism. The agro-tourism that will be developed in Carik Injeman Land is Sustainable Agrotourism which can later be seen from the start of planting, processing and selling livestock products from the Carik Injeman Land agro-tourism. The development of this design was carried out on the basis of research using descriptive - qualitative methods with data collection methods in the form of direct observation, questionnaires and using a linkert scale. The analysis of the research obtained will be in the form of the results of community respondents regarding the design development of Carik Injeman Land, Cibodas Village. The results of the research will be in the form of Agrotourism Design that still maintains natural resources and also local resources that exist in Cibodas Village.